THE SITUATION OF PRATICE CERVICAL CANCER PREVENTION AMONG REPRODUCTIVE AGE WOMEN AND HAVING GYNECOLOGICAL EXAMINATION AT LAM DONG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2021)
Objectives: The aims of this study to assess the practice of preventing cervical cancer of 15 - 49 years old and having gynecological examination women at Lam Dong General Hospital. Research method: A cross-sectional description. Interviewed practice about cervical cancer prevention of 400 women. Results: Over the course of the study, 400 women showed the number of women who had not been vaccinated is still high at 85.5%, the rate who had not been screened for cervical cancer is 62.3%. Based on the results of the study, we recommend that reproductive age women should be communicated more frequently about HPV vaccination and periodic cervical cancer screening to prevent cervical cancer.
Keywords: Cervical cance, prevention, reproductive age women